Does the benefit from statin therapy extend beyond 5 years? - Bulbulia, R; Armitage, J (2013)
Large randomized trials have shown that lowering the concentration of LDL cholesterol with statins reduces vascular morbidity and mortality rapidly, with further benefit emerging during each year of treatment allocation. But, limited evidence is available about the long-term efficacy and safety of statin treatment. Long-term follow-up of surviving trial participants allows direct assessment of the benefits (and any hazards) of a sustained reduction in LDL cholesterol concentration during the post-trial period. Post-trial follow-up of several large statin trials (of which the Heart Protection Study was the largest) confirms that the substantial absolute benefits and cost-effectiveness of statin therapy were, in fact, underestimated in previous analyses restricted to the "in-trial" periods of randomized studies. Reassuringly, no adverse effects on cancer incidence or non-vascular mortality emerged during the extended follow-up of the Heart Protection Study. These findings support the prompt initiation and long-term continuation of statin therapy in individuals at increased vascular risk.